The revolution within: ICT and the shifting knowledge base of the world's largest companies - Mendonça, S. (Economics of Innovation and New Technology, 2006)
This empirical article analyses the importance of information and communications technologies (ICT) in the technological diversification trend among the world's largest manufacturing firms during the 1980s and 1990s. The objective of the research is twofold: first, to emphasise the emerging differences among technologies when companies from different industries patent outside their traditional technological capabilities; secondly, to investigate whether the tendency among large companies from all industries to patent in ICT is distinctive when compared with the tendency to patent in other technologies. We find that technological diversification in large companies has clearly occurred in ICTs. Non-ICT specialist industries increasingly develop, rather than just utilise, the cluster of ICT-related technologies. We conclude that the development of corporate capabilities in the key technologies of the emerging ICT paradigm is more widespread than previously emphasised in the literature. One implication of this observation is that technological diversification and the information revolution may be related phenomena.